Incessant Bilobed Thymus in an Case Report Old Male Cadaver - KC, Sudikshya; Shah, Aashish Kumar; Khaling, Dipa Rai (Med Phoenix, 2017)
Thymus is bilobed primary lymphoid organ situated in superior and anterior mediastinum. The appearance of thymus varies considerably with age. It reaches maximum size at puberty and eventually undergoes “fibro fatty involution”, but it may persist actively to old age. Therefore, normal appearance and size of thymus have been elusive. Embryologically, it develops, as two separate organs from the endoderm of third pharyngeal pouches of embryo in common with inferior parathyroid glands and fuse in the midline. The study was carried on 10 embalmed cadavers of known sex in Anatomy Department of National Medical College, Birgunj, Nepal. We found a large bilobed thymus in about 65 year old male cadaver. This fact is clinically important to make differential diagnosis of radiological review in cases of mediastinal mass. A thorough knowledge of its anatomical and embryological features of the thymus, it’s normal variations, incessant in adults is necessary before doing any therapeutic, diagnostic and invasive procedures. Med Phoenix Vol.2(1) July 2017, 67-70